A Novel Immediate Nipple Reconstruction Technique in Oncoplastic Breast Surgery: Inverted Lotus Bud Flap - Burusapat, Chairat (Plast Reconstr Surg Glob Open, 2020)
Oncoplastic surgery is widely popular due to its ability to achieve curative tumor resection and symmetry of both breasts, and as a result of reduced psychological distress after mastectomy. Immediate nipple reconstruction was discussed and the gold standard procedure is inconclusive. Immediate nipple reconstruction with simultaneous breast reconstruction provides satisfactory esthetic results, compared with the delayed procedure. The “inverted lotus bud flap” was demonstrated as a new technique for immediate nipple reconstruction. The advantage of this technique is adequate nipple projection with minimization of scarring. In conclusion, oncoplastic breast surgery with immediate nipple reconstruction was demonstrated to be a safe and esthetically reliable procedure, leading to reduced psychological distress. This single-stage procedure promotes psychosocial well-being after breast cancer surgery. Immediate nipple reconstruction using the “inverted lotus bud flap” technique is versatile, reliable, and offers good esthetic results.